Continuous urea-molasses supplementation for Sumatra thin tail ewes grazing in rubber plantation : Reproductive performances. - Simon P Ginting; L.P Batubara; M.D Sanchez; K.R Pond (Jurnal Ilmu Ternak dan Veteriner, 1999)
The reproductive responses of local Sumatra ewes on the continuous urea-molasses supplementation was studied in 116 ewes for 21 months. The animals were divided into two groups and randomly allocated to urea-molasses supplement and grazing in rubber plantation or grazing in rubber plantation only (control). Both groups were allowed to graze for 8 hours a day. The urea-molasses mixture contained 3% urea (kg/kg) and were fed to the supplemented ewes ad libitum. The number of lambs born from supplemented ewes were greater than control (166 vs 114 heads). This was associated with the higher (P<0.05) litter size and the shorter lambing interval of supplemented ewes compared to those of unsupplemented ewes (1.34 vs 1.24, and 216 vs 232 d, respectively). Birth weight were not different (P>0.10) between the treatments (1.79 vs 1.61 kg), but weaning weight of lambs born to the supplemented ewes were greater (P<0.05) than the unsupplemented ewes (8.90 vs 7.55 kg). The ewe’s weight after parturition and the weight of lambs weaned per year were also greater (P<0.05) in the supplemented group compared to the control (22.7 vs 20.6 kg and 20.2 vs 15.1 kg, respectively). It was concluded that urea-molasses mixture was a good feed supplement for ewes grazing in rubber plantation. The urea-molasses supplementation clearly had positive effects on ewe and lamb productivity.   Key words : Urea, molasses, ewes, reproductive performances